The misplaced genus Trischidocera Villeneuve (Diptera, Tachinidae) - Nihei, Silvio S. (Zootaxa, 2015)
Trischidocera Villeneuve, 1915 includes two species, T. sauteri Villeneuve, 1915 (Taiwan and Malaysia) and T. yunnanensis Chao & Zhou, 1987 (China). The systematic placement of Trischidocera has been controversial. It was originally placed within the “Thryptoceratidae” (= “Actiidae”), then moved to Germariini, then considered an unplaced Tachinidae, and more recently placed in Ormiini. Here, the genus is revised, the type-species is redescribed and illustrated, and its systematic placement is discussed. The genus is removed from Ormiini and considered incertae sedis.